2021
DOI: 10.3390/nu13113800
|View full text |Cite
|
Sign up to set email alerts
|

High Dose of Caffeine Mouth Rinse Increases Resistance Training Performance in Men

Abstract: Caffeine mouth rinsing (CMR) has been shown to enhance exercise performance. However, no studies have analyzed the effects of different dosages of CMR on muscular performance. Therefore, the purpose of this study was to examine the effects of different dosages of CMR on strength (bench press 1 repetition maximum (1-RM)) and muscular endurance (60% of 1-RM repetitions to failure) in resistance-trained males. Fourteen resistance-trained males (age: 23 ± 2 years, height: 179 ± 3 cm, body mass: 83 ± 4 kg, BMI: 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The most used EA to improve resistance strength performance was CAF, which helped to improve repetitions until failure in lower body exercises. Something similar is shown in the literature, although most studies in men focus on bench presses or upper body exercises to measure this parameter [ 86 , 87 , 88 ]. As for BA, no significant results can be drawn regarding the effects of this EA on strength enhancement in women.…”
Section: Discussionmentioning
confidence: 68%
“…The most used EA to improve resistance strength performance was CAF, which helped to improve repetitions until failure in lower body exercises. Something similar is shown in the literature, although most studies in men focus on bench presses or upper body exercises to measure this parameter [ 86 , 87 , 88 ]. As for BA, no significant results can be drawn regarding the effects of this EA on strength enhancement in women.…”
Section: Discussionmentioning
confidence: 68%
“…Despite no overall effect, 5 studies showed ergogenic effects (3,8,34,37,56). The ergogenic effects of Caff-MR were apparent during 5 3 6-s repeated cycling sprints, 30-min self-paced cycling and arm cranking, and muscular endurance performance.…”
Section: Discussionmentioning
confidence: 99%
“…Across studies that showed improvements in performance with Caff-MR (3,8,34,37,56), participants were recreationally trained, while only Sinclair and Bottoms (56) did not specify the training level of the participants. In addition, the amount of caffeine rinsed per dose varied greatly, from 0.09 to 9.00 mg/ kg.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Mouth rinsing may hold particular benefits over other methods of administration, potentially mitigating issues with side effects of ingestion which may negatively influence performance. Attributed to similar mechanisms to the action of caffeinated chewing gum in the mouth, in a small number of cases caffeine mouth rinsing has been shown to elicit performance-enhancing effects on endurance activity [ 75 , 76 ], anaerobic exercise [ 77 ], muscular strength [ 78 ] and cognitive function [ 79 , 80 ]. However, the evidence is far less convincing when compared to the body of work examining the effects of caffeinated chewing gum with a recent systematic review demonstrating benefits in only 5 of the 15 included studies evaluating physical performance, with many of the included studies having low methodological quality [ 81 ].…”
Section: Effect Of Alternative Modes Of Caffeine Administrationmentioning
confidence: 99%
“…Given that caffeine mouth rinsing holds some performance-enhancing potential, further work in this area should be considered, focusing on the frequency, duration and dose–response effects of caffeine mouth rinsing. To date, only a single study has evaluated the dose–response effect of caffeine mouth rinsing, demonstrating that a repeated 5 s rinsing of a 3% (750 mg) caffeine solution increased the number of repetitions unit failure in the bench press and reduced RPE, with no effect demonstrated with a 1% (250 mg) or 2% (500 mg) dose [ 78 ]. Results summarised in the recent systematic review on this topic have only considered doses up to 2% [ 81 ].…”
Section: Effect Of Alternative Modes Of Caffeine Administrationmentioning
confidence: 99%